1990
DOI: 10.2307/1130764
|View full text |Cite
|
Sign up to set email alerts
|

Do Infants Use Their Own Images to Locate Objects Reflected in a Mirror?

Abstract: The ability of infants to locate a toy from a mirror reflection was investigated in 3 experiments. In the first, it was found that a minority of 22-month-old infants turned to locate the toy that was the source of the reflection, and that localization of the toy occurred regardless of whether the infants' own image was visible in the mirror. The results of 2 further experiments indicated that younger infants aged 14 and 18 months rarely use mirror information to locate a toy. When they do so, they also turn wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Various measures of self-recognition have been employed including self-directed behaviour (especially touching their nose in reaction to viewing a rouge spot on it), self-naming and turning to locate an object seen in the mirror (which presumes that self is used as a spatial referent for the object's location ). Bertenthal and Fischer (1978) found that the ability to locate objects occurs before the ability to name self or direct actions to self, but Robinson, Connell, McKenzie, and Day (1990) found that object location was independent of whether the infant's image was visible in the mirror, suggesting that spatial location measures are not tapping self-recognition. Johnson (1983) found that infants would display established measures of self-recognition (e.g.…”
Section: Incorporation Of Sex-of-self Into Gender Schemamentioning
confidence: 99%
“…Various measures of self-recognition have been employed including self-directed behaviour (especially touching their nose in reaction to viewing a rouge spot on it), self-naming and turning to locate an object seen in the mirror (which presumes that self is used as a spatial referent for the object's location ). Bertenthal and Fischer (1978) found that the ability to locate objects occurs before the ability to name self or direct actions to self, but Robinson, Connell, McKenzie, and Day (1990) found that object location was independent of whether the infant's image was visible in the mirror, suggesting that spatial location measures are not tapping self-recognition. Johnson (1983) found that infants would display established measures of self-recognition (e.g.…”
Section: Incorporation Of Sex-of-self Into Gender Schemamentioning
confidence: 99%
“…These tests would determine whether Kyaaro indeed differentiated reflected from nonreflected information. Two-year-old children cannot: Although they locate reflected objects without using knowledge of their self-image (Robinson, Connell, McKenzie, & Day, 1990), they cannot distinguish between seeing themselves in a mirror and seeing a twin behind a glass plate (Zazzo, 1975(Zazzo, , 1979. The twin task demonstrated that the children not only failed at self-recognition but also that they did not understand that the mirror reflected information on their side of the frame and that glass transmitted information from the other side (Loveland, 1987).…”
Section: Habituation Trialsmentioning
confidence: 99%
“…An interesting question is whether a number of children in this age period fail to use their own image to determine an object's location, as suggested by Robinson et al (1990), or whether they use their own image as a landmark cue but fail to use it successfully. It may even be that they use their own image as a guiding cue only in the initial phases of mirror learning, but skip it once acquainted with the mirror as a reflective tool.…”
Section: Discussionmentioning
confidence: 99%
“…This sensitivity may make the spot on their face salient to them (Mitchell, 1994, p. 89;Vyt, 1995). The mark task, which is widely held to be the most valid index of visual self-recognition (Johnson, 1983;Anderson, 1984b;Robinson et al, 1990), could largely reflect this facet of the child's developing sensitivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation